Efectos del programa educación en salud y formación de hábitos saludables en docentes de primaria “Institución Educativa Indoamericano”, El Porvenir - Florian Plasencia, Ernestina Haydeé (2020)
ABSTRACT I study the present fact-finding education in Salud in the formation of healthy habits of the teachers of primary school aimed at determining the effects of the program Institution teaching his Indo - American Future, he was a descriptive cross-section study with a design experimental pre. The used method was the deductive, inductive explanatory; He had as population to 40 teachers that received the educational program in 5 educational sessions of primary level, used itself as the instrument was the questionnaire, through Likert's scale. The results according to the dimension of knowledge in education in health the 10 %. It was obtained like conclusion than 37,5 % of teachers you agreed to change the healthy habits, the 50 % acquired knowledge of the washing of hands as healthy habit.